Self perception - Riding, R. J.; Rayner, Stephen (International perspectives on individual differences, 2001)
This text offers an international perspective on contemporary theory and research in self-perception. Drawing upon an international field of established and contemporary researchers, the work presents both theoretical and applied work looking at individual difference in human performance.